The Baby K Case: A Search for the Elusive Standard of Medical Care - Schneiderman, Lawrence J. (Cambridge quarterly of healthcare ethics, 1997)
An anencephalic infant, who came to be known as Baby K, was born at Fairfax Hospial in Falls Church, Virginia, on October 13, 1992. From, the moment of birth and repeatedly thereafter, the baby's mother insisted that aggressive measures be pursued, including cardiopulmonary resuscitation and ventilator support, to keep the baby alive as long as possible. The physicians complied. However, following the baby's second admission for respiratory failure, the hospital sought declaratory relief from the court permitting it to forgo emergency life support on the grounds that “a requirement to provide respiratory assistance would exceed the prevailing standard of medical care,” and that “because any treatment of their condition is futile, the prevailing standard of medical care for infants with anencephaly is to provide warmth, nutrition, and hydration.” The United States Court of Appeals for the Fourth Circuit ruled in favor of the baby's mother, citing the federal Emergency Medical Treatment and Active Labor Act (popularly known as the “anti-dumping” act), which contained no “standard of care” exception to the requirement to provide “treatment necessary to prevent the material deterioration of the individual's condition.” An appeal to the United States Supreme Court was rejected. The baby died some two and one-half years later of cardiac arrest during her sixth visit to the emergency department of Fairfax Hospital for respiratory failure.